The cnf1 gene is associated with an expanding Escherichia coli ST131 H30Rx/C2 subclade and confers a competitive advantage for gut colonization. (31st December 2022) - Tsoumtsa Meda, Landry L.; Landraud, Luce; Petracchini, Serena; Descorps-Declere, Stéphane; Perthame, Emeline; Nahori, Marie-Anne; Ramirez Finn, Laura; Ingersoll, Molly A.; Patiño-Navarrete, Rafael; Glaser, Philippe; Bonnet, Richard; Dussurget, Olivier; et al.
ABSTRACT: Epidemiological projections point to acquisition of ever-expanding multidrug resistance (MDR) by Escherichia coli, a commensal of the digestive tract and a source of urinary tract pathogens. Bioinformatics analyses of a large collection of E. coli genomes from EnteroBase, enriched in clinical isolates of worldwide origins, suggest the Cytotoxic Necrotizing Factor 1 (CNF1)-toxin encoding gene, cnf1, is preferentially distributed in four common sequence types (ST) encompassing the pandemic E. coli MDR lineage ST131. This lineage is responsible for a majority of extraintestinal infections that escape first-line antibiotic treatment, with known enhanced capacities to colonize the gastrointestinal tract. Statistical projections based on this dataset point to a global expansion of cnf1 -positive multidrug-resistant ST131 strains from subclade H 30Rx/C2, accounting for a rising prevalence of cnf1 -positive strains in ST131. Despite the absence of phylogeographical signals, cnf1 -positive isolates segregated into clusters in the ST131- H 30Rx/C2 phylogeny, sharing a similar profile of virulence factors and the same cnf1 allele. The suggested dominant expansion of cnf1 -positive strains in ST131- H 30Rx/C2 led us to uncover the competitive advantage conferred by cnf1 for gut colonization to the clinical strain EC131GY ST131- H 30Rx/C2 versus cnf1 -deleted isogenic strain. Complementation experiments showed that colon tissue invasion was compromised in the absence of deamidase activity on Rho GTPases by CNF1. Hence, gut colonization factor function of cnf1 was confirmed for another clinical strain ST131- H 30Rx/C2. In addition, functional analysis of the cnf1 -positive clinical strain EC131GY ST131- H 30Rx/C2 and a cnf1 -deleted isogenic strain showed no detectable impact of the CNF1 gene on bacterial fitness and inflammation during the acute phase of bladder monoinfection. Together these data argue for an absence of role of CNF1 in virulence during UTI, while enhancing gut colonization capacities of ST131- H 30Rx/C2 and suggested expansion of cnf1 -positive MDR isolates in subclade ST131- H 30Rx/C2.